The influence of amphetamine on sensory and conditioned reinforcement: evidence for the re-selection hypothesis of dopamine function - Winterbauer, Neil E.; Balleine, Bernard W. (Frontiers in Integrative Neuroscience, 2007)
In four experiments we assessed the effect of systemic amphetamine on the ability of a stimulus paired with reward and a stimulus that was not paired with reward to support instrumental conditioning; i.e., we trained rats to press two levers, one followed by a stimulus that had been trained in a predictive relationship with a food outcome and the other by a stimulus unpaired with that reward. Here we show, in general accord with predictions from the dopamine re-selection hypothesis [Redgrave and Gurney (2006). Nat. Rev. Neurosci. 7, 967– 975], that systemic amphetamine greatly enhanced the performance of lever press responses that delivered a visual stimulus whether that stimulus had been paired with reward or not. In contrast, amphetamine had no effect on the performance of responses on an inactive lever that had no stimulus consequences. These results support the notion that dopaminergic activity serves to mark or tag actions associated with stimulus change for subsequent selection (or re-selection) and stand against the more specific suggestion that dopaminergic activity is solely related to the prediction of reward.